Immunological failure of first‐line and switch to second‐line antiretroviral therapy among HIV‐infected persons in Tanzania: analysis of routinely collected national data. Issue 7 (2nd April 2015) - Vanobberghen, Fiona M.; Kilama, Bonita; Wringe, Alison; Ramadhani, Angela; Zaba, Basia; Mmbando, Donan; Todd, Jim
Abstract Objectives Rates of first‐line treatment failure and switches to second‐line therapy are key indicators for national HIV programmes. We assessed immunological treatment failure defined by WHO criteria in the Tanzanian national HIV programme. Methods We included adults initiating first‐line therapy in 2004–2011 with a pre‐treatment CD4 count, and ≥6‐months of follow‐up. We assessed subhazard ratios (SHR) for immunological treatment failure, and subsequent switch to second‐line therapy, using competing risks methods to account for deaths. Results Of 121 308 adults, 7% experienced immunological treatment failure, and 2% died without observed immunological treatment failure, over a median 1.7 years. The 6‐year cumulative probability of immunological treatment failure was 19.0% (95% CI 18.5, 19.7) and of death, 5.1% (4.8, 5.4). Immunological treatment failure predictors included earlier year of treatment initiation (P < 0.001), initiation in lower level facilities (SHR = 2.23 [2.03, 2.45] for dispensaries vs. hospitals), being male (1.27 [1.19, 1.33]) and initiation at low or high CD4 counts (for example, 1.78 [1.65, 1.92] and 5.33 [4.65, 6.10] for <50 and ≥500 vs. 200–349 cells/mm3, respectively). Of 7382 participants in the time‐to‐switch analysis, 6% switched and 5% died before switching. Four years after immunological treatment failure, the cumulative probability of switching was 7.3% (6.6, 8.0) and of death, 6.8% (6.0, 7.6). Those who immunologically failed in dispensaries, health centres and government facilities were least likely to switch. Conclusions Immunological treatment failure rates and unmet need for second‐line therapy are high in Tanzania; virological monitoring, at least for persons with immunological treatment failure, is required to minimise unnecessary switches to second‐line therapy. Lower level government health facilities need more support to reduce treatment failure rates and improve second‐line therapy uptake to sustain the benefits of increased coverage.